Surface and Catalytic Properties of γ-Irradiated FeO/AlO Solids - G.A. El-Shobaky; A.S. Ahmad; A.M. Ghozza; S.M. El-Khouly (Adsorption Science & Technology, 1996)
Two specimens of Fe 2 O 3 /Al 2 O 3 solids were prepared by impregnating a known mass of finely-powdered Al(OH) 3 with calculated amounts of ferric nitrate solutions followed by drying at 120°C and calcination in air at 400°C for 4 h. The mixed solids thus prepared had the nominal molar compositions 0.06Fe 2 O 3 /Al 2 O 3 and 0.125Fe 2 O 3 /Al 2 O 3 (FeAl-I and FeAl-II). The surface and catalytic properties of various irradiated solids (15–200 Mrad) were studied using nitrogen adsorption at −196°C and catalysis of CO oxidation by O 2 at 150–280°C using a static method. The results obtained revealed that γ-irradiation at doses between 15 and 80 Mrad resulted in a progressive decrease (7–22%) in the surface area of the treated solids. Treatment with doses above this limit exerted an opposite effect. γ-Irradiation also resulted in a widening of the pores of the irradiated adsorbents. The catalytic activity of the FeAl-I solid was influenced slightly by γ-rays while the FeAl-II catalyst was significantly modified by this treatment. The reaction rate constant per unit surface area of the catalytic reaction conducted at 280°C over the FeAl-II solid decreased (65%) by exposure to doses up to 120 Mrad, then increased on increasing the dose above this limit. This did not modify the mechanism of the catalytic reaction, but changed the number of catalytically-active sites taking part in chemisorption and catalysis of the CO oxidation reaction without affecting their energetic nature.